Acute myeloid leukemia with inv(3)(q21.3q26.2)/t(3;3)(q21.3;q26.2): Study of 61 patients treated with intensive protocols. (16th June 2020) - Sitges, Marta; Boluda, Blanca; Garrido, Ana; Morgades, Mireia; Granada, Isabel; Barragan, Eva; Arnan, Montserrat; Serrano, Josefina; Tormo, Mar; Miguel Bergua, Juan; Colorado, Mercedes; Salamero, Olga; et al.
Abstract: Introduction: Inv(3)(q21.3q26.2)/t(3;3)(q21.3;q26.2) is a rare poor prognosis cytogenetic abnormality present in acute myeloid leukemia (AML) and other myeloid neoplasms. Objective: The aim of this study was to evaluate the outcome of a cohort of 61 patients with newly diagnosed AML with inv(3)/t(3;3) treated with homogeneous intensive chemotherapy protocols conducted by the Spanish PETHEMA and CETLAM cooperative groups between 1999 and 2017. Methods: In this retrospective study the main clinical and biologic parameters were collected. The complete response (CR) rate, the cumulative incidence of relapse (CIR) and the overall survival (OS) were calculated. An analysis of prognostic factors for survival was performed. Results: Sixty‐one patients received induction and only 18 (29%) achieved CR (median age, 46 years). Allogeneic hematopoietic stem cell transplantation (alloHSCT) was performed in 36 patients (59%), 15 with active disease. One‐ and 4‐year CIR were 52% and 56%. One‐ and 4‐year OS probabilities were 41% and 13%. By multivariate analysis monosomal karyotype (MK) was associated with poorer OS (HR 2.0, P  = .017). Conclusion: Inv(3)/t(3;3) AML is a poor prognosis entity with low response to standard chemotherapy and to alloHSCT because of frequent and early relapse. MK was associated with a poorer prognosis. Improved therapeutic strategies are clearly needed.